How people harness their collective wisdom and power to construct the future in co-laboratories of democracy - Christakis, Alexander N. (Research in public management., 2006)
We have all experienced the benefits of dialogue when we openly and thoughtfully confront issues. We have also experienced the frustration of interminable discussion that does not lead to progress. Co-Laboratories of Democracy enable large, diverse groups to dialogue and generate positive results. Many group processes engender enthusiasm and good feeling as people share their concerns and hopes with each other. Co-Laboratories go beyond this initial euphoria to:Discover root causes; Adopt consensual action plans; Develop teams dedicated to implementing those plans; and Generate lasting bonds of respect, trust, and cooperation.Co-Laboratories achieve these results by respecting the autonomy of all participants, and utilizing an array of consensus tools including discipline, technology and graphics that allow the stakeholders to control the discussion. These are explained in depth in a book authored by Alexander N. Christakis with Kenneth C. Bausch: Co-Laboratories of Democracy: How People Harness Their Collective Wisdom to Create the Future (Information Age, 2006).Co-Laboratories are a refinement of Interactive Management, a decision and design methodology developed over the past 30 years to deal with very complex situations involving diverse stakeholders. It has been successfully employed all over the world in situations of uncertainty and conflict. On Cyprus, for example, it has been used to bridge the divide between the Turkish and Greek factions on the island. It is currently being employed on that island to help Palestinian authorities organize their government.Co-Laboratories in one day can draw together a diverse group of people on an issue, elicit authentic feelings and respectful listening, generate agreed upon language, and identify leverage points for effective action. Participants will be able to generate a consensual action plan. Co-Laboratories generate real respect, understanding, and cooperation among participants and do it rapidly.